Faktor – Faktor yang Berhubungan dengan Kinerja Perawat dalam Melakukan Triase di IGD Rumah Sakit Kutacane - Anggara, Reno; Firdaus, Syamsul; Syafwani, M.; Ruslinawati, Ruslinawati; Muthmainnah, Muthmainnah (Universitas Malahayati, 2024)
ABSTRACT Factors originating from the nurses themselves include knowledge and abilities, work-related competencies, work motivation, and work happiness. Meanwhile, factors outside the nurse's control such as workload and organizational leadership style have a significant effect on nurse performance. This study aims to analyze the factors related to the performance of nurses in carrying out triage in the Emergency Room of Kutacane Hospital. This type of research is quantitative research with a cross sectional approach. This study involved 50 respondents selected by total sampling technique. Data collection using questionnaires and multiple logistic regression. The research instrument is to assess independent variables which include internal and external aspects. The relationship between skills and nurse performance is in the category most related to the P-value (0.000) <0.05. For nurses to be able to improve the performance of nurses in conducting triage in the Kutacane Hospital Emergency Room. The most dominant factor related to nurse performance is the skills of nurses in conducting triage in the Emergency Room of Kutacane Hospital as evidenced by the Odd Ratio of 132.0. Skills to support nurses' performance in carrying out triage in the emergency room at Kutacane Hospital. Therefore, it is hoped that hospital management can create standard operating procedures regarding the performance of nurses in carrying out triage, thereby improving the quality of service to patients being treated. which can be used as a reference by future researchers. Keywords: Nurse Performance, Triage ABSTRAK Faktor yang berasal dari perawat itu sendiri meliputi pengetahuan dan kemampuan, kompetensi terkait pekerjaan, motivasi kerja, dan kebahagiaan kerja.Sedangkan faktor di luar kendali perawat seperti beban kerja dan gaya kepemimpinan organisasi berpengaruh signifikan terhadap kinerja perawat. Faktor-faktor yang berhubungan dengan kinerja perawat dalam melalukan triase di IGD RS Kutacane. Penelitian kuantitatif dengan pendekatan cross sectional. Penelitian ini melibatkan 50 responden yang dipilih dengan teknik sampel total sampling. Pengumpulan data menggunakan kuesioner dan regresi logistik berganda.Instrumen penelitian merupakan untuk menilai variabel bebas yang meliputi aspek internal dan eksternal. Hubungan keterampilan dengan kinerja perawat berada pada kategori paling berhubungan dengan dinai P-value ( 0,000 )< 0,05. Kepada perawat agar mampu meingkatkan kinerja perawat dalam melakukan triase di IGD RS Kutacane. Faktor paling dominan yang berhubungan kinerja perawat adalah keterampilan perawat dalam melakukan triase di IGD RS Kutacane dibuktikan dengan Odd Rasio132,0. Keterampilan mendukung kinerja perawat dalam melakukan triase di IGD RS Kutacane. Oleh karena itu diharapkan pihak manajerial rumah sakit agar dapat membuat standar oprasional prosedur tentang kinerja perawat dalam melakukan triase, sehingga meningkatkan kualitas pelayanan kepada pasien yang di rawat. yang dapat dijadikan salah satu refrensi oleh peneliti dimasa mendatang. Kata Kunci: Kinerja Perawat, Triase